Energy-Efficient SAR Coherent Change Detection Based on Deep Multithreshold Spiking-UNet - Xinyi Ye; Yanxing Liu; Zihan Wang; Yizhe Fan; Bingchen Zhang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
As a branch application of the synthetic aperture radar (SAR), coherent change detection (CCD) is commonly utilized to help differentiate specific changes from the unchanged scene. To exactly pick out manmade changes of interest from change maps, the introduction of artificial neural networks (ANNs) has significantly enhanced detection performance but taken up great computational resources, making it challenging to deploy on edge devices with limited resources and a strict power budget. Spiking neural networks (SNNs) not only infer results more energy-efficiently but also have the potential to drive ultralow-power neuromorphic computers which ANNs lack. In this study, to detect coherent changes precisely and with less energy consumption, a robust SNN-based change analysis method is proposed to make it available to implement CCD tasks via the “WenTian I” brain-like computer. First, we adopt a Poisson spike encoding method based on fuzzy c-means clustering to preclassify pixels and translate continuous change maps into spikes. Second, we input the spike images into a novel deep SNN, multithreshold Spiking-UNet. By representing information in the form of sparse spike flows, our proposed change detection model can reduce the energy consumption of CCD while maintaining excellent detection capabilities. The corresponding experimental results validate the comparable detection effectiveness and superior energy efficiency of our SNN-based method used for SAR CCD.